Application of Good Governance Principles in Improving the Performance of Public Service Apparatus (Case Study at the One Stop Service Office of Jayapura Regency) - Fandli Kempa; Rijal Rijal; Irwan Irwan (Jurnal Aktor, 2021)
This study aims to determine the application of the principles of good governance in improving the performance of the public service apparatus (Case Study at the One Stop Service Office, Jayapura Regency). This study used qualitative research methods. In qualitative research, the instrument or tool of the researcher is the researcher himself. Data collection techniques were obtained through observation, interviews, literature study and documentation. The results of this study indicate that the application of the principles of good governance, namely Accountability, Transparency, Participation, and Legal Supremacy of Bureaucratic Apparatuses, shows that it has not been carried out optimally in improving the performance of the public service apparatus at the One Stop Service Office, Jayapura Regency.